2019
DOI: 10.3390/su12010001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Teachers’ Implementation of a Reformed Instructional Model in China from the Theory of Planned Behavior Perspective: A Multiple Case Study

Abstract: It is difficult for curriculum reform to achieve sustainable success without support from teachers in the front line. The authors of this paper investigated teacher factors behind the successful implementation of a reformed instructional model, the Dao Jiang Ping (DJP) model, in China. This study is part of a longitudinal project (2012)(2013)(2014)(2015)(2016)(2017) that reported the level of DJP implementation and explored factors that influence teachers' implementation. This paper mainly focuses on the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…How English teachers conceptualized the 'localization' principles in the Core Curriculum is thus critical for the quality of English education (Nomnian, 2013;Vibulphol, 2012). Factors that may explain their understanding were also examined as previous studies have shown that they can affect teachers' understanding (Ahmad, 2014;Alsubaie, 2016;Apau, 2021;Choppin 2011;Crary, 2019;Datnow, 2020;Rahman et al, 2018;Vandeyar, 2017;Zhao et al, 2020). The present study may be small in scale, but the findings could reflect the situations in many public schools in Thailand.…”
Section: Teachers' Understanding and Curriculum Implementationmentioning
confidence: 93%
See 1 more Smart Citation
“…How English teachers conceptualized the 'localization' principles in the Core Curriculum is thus critical for the quality of English education (Nomnian, 2013;Vibulphol, 2012). Factors that may explain their understanding were also examined as previous studies have shown that they can affect teachers' understanding (Ahmad, 2014;Alsubaie, 2016;Apau, 2021;Choppin 2011;Crary, 2019;Datnow, 2020;Rahman et al, 2018;Vandeyar, 2017;Zhao et al, 2020). The present study may be small in scale, but the findings could reflect the situations in many public schools in Thailand.…”
Section: Teachers' Understanding and Curriculum Implementationmentioning
confidence: 93%
“…Were teachers to have thorough knowledge of how to expertly execute the curriculum, the outcomes would be favorable. Several factors have been identified to mediate or inhibit teachers' understanding such as teachers' involvement in the curriculum implementation (Ahmad, 2014;Alsubaie, 2016;Choppin 2011;Rahman et al, 2018), teachers' beliefs and attitudes towards a new curriculum (Ahmad, 2014;Zhao et al, 2020), how the new curriculum is communicated to stakeholders (Crary, 2019;Ornstein & Hunkins, 2018;Vandeyar, 2017), opportunities for collaboration and discussion among teachers (Apau, 2021;Datnow, 2020;Ornstein & Hunkins, 2018), organizational support (Zhao et al, 2020), and witnessing positive changes in students (Zhao et al, 2020).…”
Section: Teachers As Agents In Curriculum Implementationmentioning
confidence: 99%
“…They concluded that those within the school context have a shared interpretation system that may be revealed by their "native discourse" (consisting of teachers' daily language use, concepts, and interactions). Zhao et al (2020) studied reform-based teaching practices and concluded that an atmosphere and place for interactions helped mathematics teachers put reform theories into practice. This study showed that informal interactions allow people to connect with the specific advantage of an easy understanding of language.…”
Section: Research On Teachers' Informal Interactionsmentioning
confidence: 99%
“…After years of trials and experiments to improve teaching, the country is still developing effective and innovative teaching skills. The LPG organizes activities to try out new teaching strategies and pedagogical ideas that align with the implementation of educational reform (Zhao et al, 2020). However, teachers must realize a common goal for understanding and developing skills under the new paradigm, such as teaching through collaborative mathematics problem-solving activities, to improve academic performance levels.…”
Section: Shared Goals Guide the Content Of Informal Interactionsmentioning
confidence: 99%
“…Yet, it is difficult for educational reforms to achieve sustainable success without needed support from teachers in the front line (Fullan, 2001;Schoenfeld, 2014). However, it is widely Transforming curriculum reform ideas reported that teachers found it challenging to put reform ideas into classroom practices (Buchs et al, 2017;Zhao et al, 2019). Lesson study (LS), a teacher-oriented, student-focused teacher collaboration approach, has been documented to play critical roles in implementing reform-oriented teaching (Lewis and Takahashi, 2013).…”
Section: Introductionmentioning
confidence: 99%